2013
DOI: 10.1111/gcbb.12146
|View full text |Cite
|
Sign up to set email alerts
|

Increased energy maize production reduces farmland bird diversity

Abstract: Producing energy crops as an alternative to fossil fuels in order to reduce CO 2 emissions will lead to large-scale changes in agricultural landscapes. Here, we quantify the potential impact of an increase in maize fields on the diversity of farmland birds by means of high resolution (25 9 25 m) land-use scenarios. We generated scenarios in which the area of maize production in Germany increases from presently 2.6 to 2.9, 3.6 and 4.3 million ha, corresponding to the energy crop production targets of the German… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 63 publications
2
31
0
Order By: Relevance
“…[14,15]). A number of spatially explicit modelling studies have also emerged to evaluate the biodiversity responses from energy crop production at regional, national and pan-national scales, maize in particular [16][17][18][19], some of which considered land-use change scenarios involving energy crop cultivation on marginal land of high nature value [20,21]. In addition, many field-scale or empirical studies with a focus on a particular energy crop have been conducted to compare biodiversity impacts with those of row crops or grasslands [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…[14,15]). A number of spatially explicit modelling studies have also emerged to evaluate the biodiversity responses from energy crop production at regional, national and pan-national scales, maize in particular [16][17][18][19], some of which considered land-use change scenarios involving energy crop cultivation on marginal land of high nature value [20,21]. In addition, many field-scale or empirical studies with a focus on a particular energy crop have been conducted to compare biodiversity impacts with those of row crops or grasslands [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…This has resulted in a scattering of decentralised bioenergy plants across the landscape, mainly due to their dependency on spatially diffuse biomass resources. Such configurations of biomass and bioenergy technologies in the landscape make the influence of bioenergy production obvious to the eye (e.g., maize and biogas plant dominated landscapes [4]) and thus open to scrutiny for a broad list of potential environmental burdens 1 , to soil, to water, and land use [5][6][7][8]. In general, life cycle assessment (LCA) is the most popular assessment approach used for investigating the environmental burdens associated with bioenergy production [9][10][11].…”
Section: Assessments Of Bioenergy Systemsmentioning
confidence: 99%
“…With many burdens of bioenergy production strongly influenced by the regional variability (e.g., management, climate, soil) of biomass production [5,6,23,24,[26][27][28], O'Keeffe et al [19] identified the need to begin determining what is happening "within" a regional context for a bioenergy producing region. They also identified that life cycle thinking framed in a regionally contextualised manner is at a nascent stage, particularly with regard to implementing a suitable or appropriate life cycle impact assessment phase 4 . For this reason it was suggested, as a first step, to begin exploring regionally contextualised life cycle thinking with the development of life cycle inventory assessments.…”
Section: Regionally Contextualised Life Cycle Thinkingmentioning
confidence: 99%
See 1 more Smart Citation
“…The following two articles focus on the response of farmland birds to an expansion of maize cultivation for biogas at the landscape scale (Everaars et al ., and Sauerbrei et al ., ). Both studies apply spatially explicit modeling approaches, either using a generated model landscape (Everaars et al ., ) or a map of recent land use in Germany (Sauerbrei et al ., ) as the reference for different scenarios of increased maize cultivation. They arrive at the congruent finding that expanded maize cultivation and related homogenizing of landscape structures reduces breeding bird density.…”
mentioning
confidence: 97%